Some psychological aspects of relationship between examiners and students - Novodvorskis , A. (Psichologija, 1972)
Examination is to be considered one of the main forms for checking students’ knowledge and teaching quality. Its efficiency is dependent upon many factors among which the relations between examiners and students during the examination are of great importance. A great deal of attention would be worth devoting to these relations, first of all from the psychological point of view. Examination methods ought to provide conditions enabling the most objective judgement about the students’ actual knowledge. Its estimation must be entirely objective and satisfy the requirements raised to the students. During the examination equal conditions for a successful passing must be insured for every student. These conditions depend upon the climate and surroundings of the examination, the techniques of inquest, etc. On the basis of the studies carried out, as well as of the author's own experience the analysis of some psychological aspects of relationship between examiners and their students is given. Use of concrete examples has been made in this analysis.
Keywords: examination; relationship; psychological aspects